Microbial biochemical pathways of arsenic biotransformation and their application for bioremediation - Mohsin, Hareem; Shafique, Maria; Zaid, Muhammad; Rehman, Yasir (Folia microbiologica, 2023)
Arsenic is a ubiquitous toxic metalloid, the concentration of which is beyond WHO safe drinking water standards in many areas of the world, owing to many natural and anthropogenic activities. Long-term exposure to arsenic proves lethal for plants, humans, animals, and even microbial communities in the environment. Various sustainable strategies have been developed to mitigate the harmful effects of arsenic which include several chemical and physical methods, however, bioremediation has proved to be an eco-friendly and inexpensive technique with promising results. Many microbes and plant species are known for arsenic biotransformation and detoxification. Arsenic bioremediation involves different pathways such as uptake, accumulation, reduction, oxidation, methylation, and demethylation. Each of these pathways has a certain set of genes and proteins to carry out the mechanism of arsenic biotransformation. Based on these mechanisms, various studies have been conducted for arsenic detoxification and removal. Genes specific for these pathways have also been cloned in several microorganisms to enhance arsenic bioremediation. This review discusses different biochemical pathways and the associated genes which play important roles in arsenic redox reactions, resistance, methylation/demethylation, and accumulation. Based on these mechanisms, new methods can be developed for effective arsenic bioremediation.
Keywords: Oxidation-Reduction; oxidace-redukce; biodegradace; lidé; Bacteria; Humans; Biodegradation, Environmental; Biotransformation; Arsenic; arsen; biotransformace